STRATEGI OPTIMALISASI PENGHIMPUNAN DANA NASABAH BAGI PERKUATAN PERMODALAN DI BMT MAWADDAH KANTOR CABANG PANDAAN PASURUAN - Aulia Laita M; Renny Oktafia (IAIN Syekh Nurjati Cirebon, 2020)
AbstractThe purpose of this study was to determine the strategy for optimizibg customer fund collection at BMT Mawaddah Kantor Cabang Pandaan Pasuruan Branch Office. The method used in this reserach is qualitative method. Data collection techniques used in thid study are observation, interviews and documentation. The result of this research is BMT Mawaddah Pasuruan Branch Office in managing customer funds the strategy used is a pick-up system to pomote products owned by BMT Mawaddah to the community.